2021
DOI: 10.3390/bios11080266
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aptamer Functionalized Hydrogels for Interferometric Fiber-Optic Based Continuous Monitoring of Potassium Ions

Abstract: In the present paper, we describe a potassium sensor based on DNA-aptamer functionalized hydrogel, that is capable of continuous label-free potassium ion (K+) monitoring with potential for in situ application. A hydrogel attached to the end of an optical fiber is designed with di-oligonucleotides grafted to the polymer network that may serve as network junctions in addition to the covalent crosslinks. Specific affinity toward K+ is based on exploiting a particular aptamer that exhibits conformational transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In some studies, hydrogels with specific stimulus responsiveness were wrapped at the end of the fiber to form the interference structure. When the stimulation conditions were reached, the expansion or contraction of the hydrogel changed the wavelength of light in the fiber, [204][205][206][207] enabling target detection (Figure 17a). For example, ambient humidity could be measured by the interference structure of optical fibers wrapped with a strongly hygroscopic hydroxypropyl methylcellulose hydrogel.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, hydrogels with specific stimulus responsiveness were wrapped at the end of the fiber to form the interference structure. When the stimulation conditions were reached, the expansion or contraction of the hydrogel changed the wavelength of light in the fiber, [204][205][206][207] enabling target detection (Figure 17a). For example, ambient humidity could be measured by the interference structure of optical fibers wrapped with a strongly hygroscopic hydroxypropyl methylcellulose hydrogel.…”
Section: Othersmentioning
confidence: 99%
“…For example, ambient humidity could be measured by the interference structure of optical fibers wrapped with a strongly hygroscopic hydroxypropyl methylcellulose hydrogel. [204] Additionally, fibers coated with DNA aptamermodified [205] or glucose recognition agentdoped [206,207] hydrogels enabled the detection of more complex targets, such as K + and glucose. In another method, hydrogel films with specific stimuli-responsiveness covered the surface of a metal sensor with a glass substrate to [197] c) Hydrogel microspheres immobilized with recombinant E. coli are used to detect heavy metals in water, each microsphere is wrapped in a tough semi-permeable hydrogel shell to prevent leakage of engineered bacteria.…”
Section: Othersmentioning
confidence: 99%
“…This ability to regulate the K + -specific aptamer enables the aptasensor to have higher sensitivity and adaptability in a variety of practical applications. 57–60…”
Section: Aptamer Biosensors For K+ Detectionmentioning
confidence: 99%
“…This ability to regulate the K + -specific aptamer enables the aptasensor to have higher sensitivity and adaptability in a variety of practical applications. [57][58][59][60] Unfortunately, a full-length review article on aptamer-based biosensors for K + detection has not been reported yet. This review offers an extensive overview of the latest developments in aptamer-based biosensors for K + detection over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Pure hydrogels are composed exclusively of DNA molecules and bind through, among others, Watson-Crick base-pair interactions, enzymatic ligation, and enzymatic polymerization [ 200 ]. Some of their most recent applications are their use in capillary assays for the optical detection of short cDNA from the SARS-CoV-2 virus [ 201 ], as potassium ion monitoring sensors with potential for in situ applications [ 202 ], such as hydrogel sensors integrated with quantum dot-linked transcription factors for quantitative detection of progesterone [ 203 ], among others.…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%